EFFECT OF DIFFERENT DOSE OF VITAMIN E ADDED TO FEED DIET ON GONAD MATURATION OF CLIMBING PERCH (Anabas testudineus Bloch) - Nopri Bangun Harahap; Netti Aryani; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted from September-November 2014 at the Fish Hatchery and Breeding Laboratory Faculty of Fisheries and Marine Science University of Riau. The objective of the research was to examine the optimal doses of vitamin E added to feed diet on the gonad maturation of the climbing perch (Anabas testudineus Bloch) such as Gonad Maturation Level, Gonad Somatic Index (GSI), fecundity and egg diameter. A completetely randomized design with three replicationwas used and four treatments.The treatmen in this research were P0 (pellet+Vit E 0 mg), P1 (pellet+Vit E 150 mg), P2 (pellet+Vit E 300 mg) and P3 (pellet + Vit E 450 mg).The results of research indicate that dosage vitamin E 300 mg was the best dosage for gonad maturation, reared for 56 days and the total fish reached Gonad Maturations Level IV 14 individuals (77,78%), Index Gonad Somatic (IGS) 9,232%, fecundity of 4.010 and egg diameter 0,698mm. The temperature range from 26-280C, pH 5-6 and DO 4-5 ppm.Keyword : Vitamin E, Gonad Maturation, Climbing Perch (Anabas testudineus Bloch)